(untitled) (Human Factors in Design, 2023)
University networks strengthen scientific and interdisciplinary development. The objective of this study is to discuss the integration between UFPR and UDESC for the improvement of Assistive Technology. From the method of temporal historical review, between 2016 and 2023, the theses and dissertations developed by the LABERG/UFPR and Li2TA/UDESC laboratories are surveyed. Twenty-eight researches were found and categorized, based on ISO 9999:2016. The results of the review indicated that the laboratories could develop new research regarding the User-Centered Design method, through the experience of projects of artifacts, tools and devices developed at universities.